A Study on the History of Chalukya Dynasty: Exploring the Rise and Independence of the Badami Chalukyas (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The Chalukyadynasty was an Indian royal dynasty that ruled large parts of southern and centralIndia between the 6th and the 12th centuries.During this period, they ruled as three related yet individual dynasties. Theearliest dynasty, known as the "Badami Chalukyas", ruled from Vatapi(modern Badami) from the middle of the 6th century. The BadamiChalukyas began to assert their independence at the decline ofthe Kadamba kingdom of Banavasi and rapidly rose toprominence during the reign of Pulakesi II.